2018
DOI: 10.11613/bm.2018.020902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Barricor™ vs. lithium heparin tubes for selected routine biochemical analytes and evaluation of post centrifugation stability

Abstract: IntroductionObtaining suitable results unaffected by pre- or postanalytical phases is pivotal for clinical chemistry service. We aimed comparison and stability of nine biochemical analytes after centrifugation using Barricor™ plasma tubes with mechanical separator vs standard Vacutainer® lithium heparin tubes.Materials and methodsWe collected samples on six healthy volunteers and nine patients from intensive care units into 6 mL plastic Vacutainer® lithium heparin tubes and 5.5 mL plastic Barricor™ plasma tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
3
13
0
3
Order By: Relevance
“…First, it has a mechanical separator instead of a gel barrier, allowing cells to pass across the separator while gels occlude this pathway. Concordant previous studies reported an acceptable correlation between Barricor™ tube results for many biochemical analytes with those of tubes used routinely such as regular lithium heparin [2], plasma separator tube (PST) or serum with (SST) or without gel barrier [1,15], although another study reported some bias when compared to tube without additive [16]. Second, the shortened centrifugation time with high speed as recommended by BD (4000xg for 3 min for Barricor™ tubes vs 2000xg for 10 min for lithium heparin tubes), does not seem to affect the results as shown by several studies [1,17].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…First, it has a mechanical separator instead of a gel barrier, allowing cells to pass across the separator while gels occlude this pathway. Concordant previous studies reported an acceptable correlation between Barricor™ tube results for many biochemical analytes with those of tubes used routinely such as regular lithium heparin [2], plasma separator tube (PST) or serum with (SST) or without gel barrier [1,15], although another study reported some bias when compared to tube without additive [16]. Second, the shortened centrifugation time with high speed as recommended by BD (4000xg for 3 min for Barricor™ tubes vs 2000xg for 10 min for lithium heparin tubes), does not seem to affect the results as shown by several studies [1,17].…”
Section: Discussionsupporting
confidence: 76%
“…Among process involved in lab TAT, the centrifugation is one of them that can be modulated. Indeed, new BD Barricor™ tubes (Becton Dickinson, NY, USA) allow a higher speed of centrifugation and therefore reduced the time of centrifugation without altering results [1,2]. So, it could be hypothesized that reduction of centrifugation time could reduce the lab TAT.…”
Section: Introductionmentioning
confidence: 99%
“…Their data show that the acceptable glucose analysis postponement was to be between 9 and 15 hours, depending on the tube used. Dupuy et al investigated the stability of nine analytes in BD lithium heparin tubes and BD Barricor tubes and they observed an AST activity increase after a 24-hour storage period in both BD lithium heparin (4.4%) and BD Barricor (5.6%) tubes, which is consistent with our results ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…2) [14]. A promising alternative to glycolysis inhibitors might be the use of mechanical barriers in lithium heparin tubes [15] as well as the use of gel barrier tubes containing lithium heparin [14], when rapid centrifugation in swing-out rotors at the site of blood drawing is feasible.…”
Section: Discussionmentioning
confidence: 99%